Transforming Geography with Geospatial Technologies - Narinder Kumar (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
This paper explores the transformative impact of geospatial technologies in the field of geography. The specific objectives of the study include describing the role of main geospatial technologies, such as Geographic Information Systems (GIS), the Global Positioning System (GPS), and Remote Sensing in contemporary geographical research. The study highlights the diverse applications of these technologies across various fields, examines future trends and emerging technologies, and reveals their potential impacts on geographical research and practices. Additionally, this paper assesses the challenges and limitations in the adoption and implementation of these technologies. Methodologically, the study is based on an extensive review of existing literature, including research papers from national and international journals and various books. The paper is structured into four sections, Section I covers GIS, Section II discusses GPS, Section III elaborates on Remote Sensing, and Section IV provides the conclusion. The discussion of the paper reveals that Geospatial technologies have revolutionized geographical research. GIS has transformed spatial data visualization, analysis, and interpretation, becoming essential in diverse fields. Likewise, GPS technology provides unparalleled accuracy in positioning and data collection, enhancing our knowledge through applications in numerous fields. Besides, Remote sensing’s ability to gather extensive data about the earth’s surface and atmosphere is vital for environmental monitoring, disaster management, urban planning and infrastructure development, agriculture, etc. The integration of these technologies has led to significant innovations in geography, promising further advancements as addressed challenges related to data interpretation, signal interference, privacy, and ethical considerations. Holding and overcoming these challenges is crucial for realizing the full potential of GIS, GPS, and Remote Sensing in progressing geographical research.